Peran Citra Destinasi Dalam Meningkatkan Niat Wisatawan Berkunjung Kembali (Studi Kasus Pada Pengunjung Puncak Darma Geopark Ciletuh Kabupaten Sukabumi) - nurhayati, nendeh - (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.10.TAHUN 2019, 2019)
The purpose of this study is to measure roles. The variables of this study are Cognitive Destination Image (X1), Unique Destination Image (X2), and Affective Destination Image (X3). The method used in this study is Quantitative and Descriptive Associative research methods. And by doing 100 online spreads for tourists who have visited the Puncak Darma Geopark Ciletuh. The analysis technique used is path analysis or path analysis, and for hypothesis testing is a partial statistical test (t test) and simultaneous test (F test). The results of the research that can be seen show the tourist destinations for tourist visits back at the Puncak Darma Geopark Ciletuh in the good category. The magnitude of the influence of the tourist destination image of the Puncak Darma Geopark Ciletuh on the intention of tourists to visit again after conducting simultaneous and partial testing has a positive and significant importance. The total influence is 72.7% while the remaining 27.3% is influenced by other variables not discussed in this study. Keywords: Destination Image, Tourist Revisit Intention , Puncak Darma Geopark Ciletuh.